Karakterisasi Struktur Kristal Nanopartikel Fe3O4@PEG:ZnO - Maharani, Rivia; Denny, Yus Rama; Antarnusa, Ganesha (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2025)
In this study, Fe3O4@PEG:ZnO nanoparticles were synthesized using the coprecipitation method. Synthesis is carried out to produce nano-sized materials with wide application potential. Synthesis is carried out through three stages, namely Fe3O4 production, Fe3O4 coating with polyethylene glycol (PEG-4000), and Fe3O4@PEG doping with ZnO. Characterization was carried out using X-Ray Diffraction (XRD) tests to analyze the crystallographic properties and structure of the material. The results of XRD analysis showed that the crystal size at Fe3O4 was 7,963 nm and Fe3O4@PEG:ZnO was 6.014 nm. The combination of the magnetic properties of Fe3O4 and the photocatalytic properties of ZnO makes this material have the potential for wide applications in environmental fields, such as the degradation of organic pollutants in water. This research contributes to the development of nanoparticle-based multifunctional materials that support sustainable technology, thereby providing significant benefits for applications in the energy and environmental fields.